Integrated protocol for ground and structures condition assessments using ambient vibration - Kamarudin, Ahmad Fahmy (2020)
Safety and serviceability issues on ground or structure normally arise after deterioration or damage appearances. It is worst when there is no regular maintenance program or complete engineering record to carry out the re-evaluation work. Application of ambient vibration (AV) technique is widely used on ground and structures diagnosis works, but none of an effort to integrate them into a specific protocol. The main goal of this thesis is to develop a robust integrated condition assessment protocol on ground and structure using ambient vibration and the main assessment parameter of origin natural frequency. AV testing was performed using a tri-axial seismometer on ground and reinforced concrete (RC) school buildings, with different geotechnical profiles, building configurations and structural health conditions. Determination of peak natural frequency was computed based on the popular methods of Horizontal to Vertical Spectral Ratio (HVSR) and Fourier Amplitude Spectra (FAS) via GEOPSY software. Started by ground condition assessment protocol, the soil classification, soil thickness, and microzonation maps were determined for local soil condition. Meanwhile, in structural condition assessment protocols, the evaluations were made on rocking effect, soil-structure resonance, structural health monitoring (SHM), and building vulnerability. The analysis was initiated by validation of HVSR method on ground, and verification of FAS method on 4-storey of RC buildings. HVSR has proven to be the reliable method. From repetitive AV measurements had indicated consistent prediction with less than 7.0 % disparity of fundamanetal ground frequency (Fo). FAS method showed 0 % of difference at the first mode of predominant building frequency (fo) prediction and 9.5 % at the fifth fo, with the comparison made to prior research. Microzonation map successfully described the sub-surface profile and the resonance zone. Good health of buildings was obtained in repetitive AV measurement within 1.5 years of maximum gap. In rocking effect protocol, the existence of friction piles was clearly identified. Illustrations of mode shapes at respective fo explained the influence of adjacent building, mass and geometric irregularities. A nomograph was introduced for quick evaluation of several components in the integrated protocols at the end analysis. In conclusion, the developed integrated protocol has demonstrated a novel, reliable and robust condition assessment. It will benefit to any ground and comparable RC building even without complete engineering database.